2016
DOI: 10.1111/ter.12213
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature concentration of tellurium and gold in continental red bed successions

Abstract: There is very little understanding of tellurium (Te) distribution and behaviour in sedimentary rocks. A suite of 15 samples of reduction spheroids (centimetre-scale pale spheroids in otherwise red rock), including samples from eight localities in Triassic red beds across the British Isles, were mapped for Te using Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry. Almost all showed enrichment in Te in the cores of the spheroids relative to background red bed concentrations, by up to four orders of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The lack of comparable reoxidation or other diagenetic overprinting in reduction spheroids within other red beds may be attributable to the relatively extensive deep burial and diagenesis of the Tumblagooda Sandstone, which is discussed in the next section. This contrasts with roscoelite-bearing reduction spheroids from various localities that are interpreted to have been exposed to maximum burial temperatures of <150 °C or present evidence of limited basinal fluidrock interaction (Hanly et al, 2003;Parnell et al, 2015b;Parnell et al, 2016;Parnell et al, 2018). Additionally, Fe-enrichment and the formation of Fe-oxide phases must have occurred during diagenesis; after the weathering of K-feldspar grains.…”
Section: Reduction Spheroid Reoxidationmentioning
confidence: 96%
See 1 more Smart Citation
“…The lack of comparable reoxidation or other diagenetic overprinting in reduction spheroids within other red beds may be attributable to the relatively extensive deep burial and diagenesis of the Tumblagooda Sandstone, which is discussed in the next section. This contrasts with roscoelite-bearing reduction spheroids from various localities that are interpreted to have been exposed to maximum burial temperatures of <150 °C or present evidence of limited basinal fluidrock interaction (Hanly et al, 2003;Parnell et al, 2015b;Parnell et al, 2016;Parnell et al, 2018). Additionally, Fe-enrichment and the formation of Fe-oxide phases must have occurred during diagenesis; after the weathering of K-feldspar grains.…”
Section: Reduction Spheroid Reoxidationmentioning
confidence: 96%
“…The metabolic processes of dissimilatory metal-reducing bacteria (DMRB) consuming organic matter in the sediment are believed to be critical in the formation of reduction spheroids. Organic matter is used by these bacteria as an energy source and reductant to allow for the bacterially-mediated reductive precipitation of dissolved metals into the cores of reduction spheroids (Spinks et al, 2010;Spinks et al, 2014;Parnell et al, 2016). As such, reduction spheroids are believed to also be of use as a potential biomarker for recording the early colonisation of the terrestrial biosphere by metal-reducing bacteria and in the search for life in the Martian geological record (Spinks et al, 2010;Thompson et al, 2014;Parnell et al, 2015a;Spinks et al, in review).…”
Section: Introductionmentioning
confidence: 99%
“…Tellurium is typically associated with deep marine ferromanganese crusts [2][3][4] and as such has been considered as a target for deep sea mining operations. However, Te has been previously suggested to concentrate in low-temperature sedimentary environments, controlled by redox variations and forming inclusions in sulphide minerals and red bed successions [5,6]. This suggests that Te may locally concentrate across sediments.…”
Section: Introductionmentioning
confidence: 92%
“…Ochre sediments and yellow soils do not host Au above level of detection. Given the presence of Au in whole rock, waste, and weathered samples, it is possible to identify potential Au pathfinder elements across Parys Mountain samples, as previous studies have shown that Se and Te can also act as Au pathfinder elements [48][49][50][51][52][53]. Figure 9 shows that Se, Bi, Cd, and Hg have a positive correlation with Au, and can act as pathfinder elements for Au in natural and waste soils and clays at Parys Mountain.…”
Section: Whole Rock and Sediment Geochemistry (Icp-aes And Icp-ms)mentioning
confidence: 99%
“…Selenium can act as a pathfinder element in Au exploration worldwide in selenide-containing epithermal Au-Ag and massive sulphide deposits [49,51,52,79]. Tellurium can also fix Au in telluridebearing Au ore deposits in a range of settings [51,53,79] Other elements that show concentrations higher than typical cut-off grades include Pb in RWSS, with an average of 1.18% in Parys Mountain RWSS compared to a cut-off grade of 1% [77], and Cu and Fe in ochre sediments (Cu = 0.29% average concentration in ochre sediments compared to a cutoff value of 0.15% [76], and Fe = 33.32% average concentration in ochre sediments compared to a cutoff value of 27.78% [74]). Resource estimate for Pb in RWSS is 3346 tonnes.…”
Section: Economic Considerationsmentioning
confidence: 99%